Perspectives: University of Haifa Israel Studies - Mayer, Gabriel (Advances in Social Sciences Research Journal, 2019)
University of Haifa International School offers an MA in Israel Studies over an approximately one-year period. As a final exam exercise, the student is asked to write an essay describing his/her interaction with the Israel national narrative as taught in courses and experienced during field trips and personal interactions with the surrounding land and landscapes, museums, archeological sites and living “inside the Judaic calendar” for the whole year. In effect, the student’s encounters may be summed up as an interface with memoryscape. The following is one student’s interpretation of this assignment. The scope of this work is an exploration of the Israel narrative, as it was shaped from the early settlement years into the modern and complex State of Israel. My ambition is to trace the early settlement periods, let’s say counting from the late 1880’s, through the development of Eretz Israel into the Jewish homeland, a concept that seemed like the story of the “impossible dream.” Over the course of my studies, we were presented with many “up close” views of the historical markers that are present in this narrative. No textbook reading alone can equal the experience a student has when history can be seen from a local, palpable and “up-front” viewpoint.